Human and Idea in the polyphonic novel: Blood and Fire’s Tetralogy of Abdolmalek Mortadh as a model - Abdelouahab, Mamoun; Abdelhafid, Tehirichi (Arab Journal for Sciences and Research Publishing, 2020)
Our research entitled “the human / the idea in the polyphonic novel, the example of « Blood and Fire’s Tetrology » of Abdolmalek Mortadh, is studying a new technique that appears in modern times, the dialogism that’s resulting from the romantic polyphony, which is working on the variation of thoughts, on perceptions and ideological visions arising from the characters.Our subject focuses mainly on the way from which the character/ Idea’s image is formed in Abdolmalek Mordadh’s narrative discourse. Besides, we will reveal the variety of provocative styles used as a writing technique by the writer, and that's for a purpose of extractionThe hero’s word about him, and about the surrounding community, which sometimes came in the form of internal dialogues between the hero and himself, then between the hero and a fictional character from his imagination.At other times, it came in the form of external dialogues Between the hero and other characters, all these dialogues in its different forms and multiple elements contributed to the formation of the hero's character, to saying his word and revealing it.The author Abdolmalek Mortadh relied on that strategy to impart objectivity in the visions and perspectives of the novel's characters in order to achieve the free and democratic nature of dialogism that the critic and theorist Mikhail Bakhtine has invited to adopt it in his encyclopedic work “Problems of Dostoevsky’s poetics”.The formation of the hero's image in the various methods adopted by the writer will inevitably make him a human with an idea, thus, he will make his novel a vast arena in which ideas interact and wrestle in a democratic and pluralistic atmosphere and his characters will turn into a set of ideas and ideologies each of them tries to stand out and appear at the expense of the other without the slightest interference by the writer, That is the focal point of the polyphonic novel.
Keywords: The Novel; The Dialogic Novel; Dialogic; Abdelmalek Mortad; Plural of Voices